Estimating the ability of pre-service and in-service Teacher Profession Education (TPE) participants using Item Response Theory - Lian Gafar Otaya; Badrun Kartowagiran; Heri Retnawati; Siti Salina Mustakim (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2020)
This research generally aimed to describe the characteristic of the ability of Pre-service and In-service TPE participants using the Item Response Theory, IRT. The research subject comprised 516 participants divided into 239 participants of the Pre-service TPE program and 277 participants of the In-service TPE program using the purposive sampling technique. Data were collected through the technique of observation and documentation. In estimating the item parameter and ability parameter, the IRT model polytomous was implemented, which was furthermore described. This finding shows that the assessor could directly recognize the position of the ability of students in the TPE program based on the item characteristic and the ability between the highest and the lowest grade in the ability scale, so this finding did not only support the implementation of TPE program in Indonesia, but also its applicability was expected to revise the assessment of teachers’ performance, the supervision of teachers, field teaching practice, and the assessment in the other teaching fields, so it could be used as an evaluation in revising the assessment model.